Multi‐omics analysis of xylem sap uncovers dynamic modulation of poplar defenses by ammonium and nitrate. (27th May 2022) - Kasper, Karl; Abreu, Ilka N.; Feussner, Kirstin; Zienkiewicz, Krzysztof; Herrfurth, Cornelia; Ischebeck, Till; Janz, Dennis; Majcherczyk, Andrzej; Schmitt, Kerstin; Valerius, Oliver; Braus, Gerhard H.; Feussner, Ivo; et al.
SUMMARY: Xylem sap is the major transport route for nutrients from roots to shoots. In the present study, we investigated how variations in nitrogen (N) nutrition affected the metabolome and proteome of xylem sap and the growth of the xylem endophyte Brennaria salicis, and we also report transcriptional re‐wiring of leaf defenses in poplar ( Populus  ×  canescens ). We supplied poplars with high, intermediate or low concentrations of ammonium or nitrate. We identified 288 unique proteins in xylem sap. Approximately 85% of the xylem sap proteins were shared among ammonium‐ and nitrate‐supplied plants. The number of proteins increased with increasing N supply but the major functional categories (catabolic processes, cell wall‐related enzymes, defense) were unaffected. Ammonium nutrition caused higher abundances of amino acids and carbohydrates, whereas nitrate caused higher malate levels in xylem sap. Pipecolic acid and N ‐hydroxy‐pipecolic acid increased, whereas salicylic acid and jasmonoyl‐isoleucine decreased, with increasing N nutrition. Untargeted metabolome analyses revealed 2179 features in xylem sap, of which 863 were differentially affected by N treatments. We identified 124 metabolites, mainly from specialized metabolism of the groups of salicinoids, phenylpropanoids, phenolics, flavonoids, and benzoates. Their abundances increased with decreasing N, except coumarins. Brennaria salicis growth was reduced in nutrient‐supplemented xylem sap of low‐ and high‐ NO3 − ‐fed plants compared to that of NH4 + ‐fed plants. The drastic changes in xylem sap composition caused massive changes in the transcriptional landscape of leaves and recruited defenses related to systemic acquired and induced systemic resistance. Our study uncovers unexpected complexity and variability of xylem composition with consequences for plant defenses. Significance Statement: The present study reports the largest, currently available plant xylem sap proteome and metabolome databases and highlights the discovery of specialized metabolites and phytohormones in the xylem sap. This multi‐omics study links differences in nitrogen supply with changes xylem sap composition, endophyte growth and transcriptional defenses in leaves.